Teaching Cyber Resilience for Critical Infrastructure Systems (Journal of The Colloquium for Information Systems Security Education, 2017)
Successful cyberattacks will occur no matter how much money and resources are dedicated to the problem. At the same time, the sectors in the current national infrastructure have not developed an effective standard strategy to protect themselves. The paradigm we present here argues that a "cyber-resilient" strategy is an effective and cost efficient approach to protecting the critical systems that power our way of life. This paper presents both a staged approach to implementing cyber-resilient systems as well as a general curriculum and pedagogy for disseminating this knowledge.
Keywords: Cybersecurity; Cyberresilient Strategy